Successful ceftolozane/tazobactam treatment of chronic pulmonary infection with pan‐resistant Pseudomonas aeruginosa. Issue 2 (April 2015) - Soliman, Reham; Lynch, Sarah; Meader, Emma; Pike, Rachel; Turton, Jane F.; Hill, Robert L. R.; Woodford, Neil; Livermore, David M.
Abstract : Introduction: The treatment of chronic Pseudomonas aeruginosa infections is challenging, with resistance and antibiogram diversity accumulating during successive therapies. Some isolates are resistant to all licensed agents, creating treatment problems and an urgent need for new therapies. Among antibiotics in advanced development, ceftolozane/tazobactam has potent in vitro antipseudomonal activity, with low MICs even for strains with AmpC β‐lactamase‐, impermeability‐ and efflux‐mediated resistance to other β‐lactams. Case presentation: A bronchiectasis exacerbation in a 59‐year‐old man involved pan‐resistant P. aeruginosa . Meropenem/colistin therapy failed. Named‐patient ceftolozane/tazobactam 2+1 g every 8 h for 14 days restored baseline respiratory and inflammatory marker status, and the patient was discharged; the ceftolozane/tazobactam MIC was 8 µg ml −1, with most growth inhibited at 2 µg ml −1 . Conclusion: A positive outcome in this difficult infection due to an otherwise pan‐resistant P. aeruginosa is notable, especially as the patient had failed prior therapy with other agents. We urge formal evaluation of ceftolozane/tazobactam in chronic pseudomonal lung infections.